DATAWAREHOUSE DALAM MELAKUKAN MORDIBITAS PENYAKIT PASIEN RAWAT INAP DI RS. DAERAH - Nia Umilizah (JURNAL INFORMANIKA, 2022)
Data mordibitas RS. Daerah berasal dari dokumen rekam medis pasien rawat inap. Laporan morbiditas pasien rawat inap dimanfaatkan sebagai evaluasi perencanaan persediaan obat, data penyakit dan dapat menjadi bahan pengambilan keputusan untuk membuat program perencanaan pembangunan kesehatan. Data pasien rawat inap yang digunakan ialah data pasien dari tahun 2018 - 2019, dengan jumlah 350 pasien. Data penyakit pasien rawat inap itulah yang diolah dengan mengunakan datawarehouse. Dari pengolahan data 10 data penyakit tersebut ialah Typoid Fever, Diarrhoea and gastroenteritis of presumed infectious orgin (Diare), Chronic renal failure, unspecifed ( GGK ), Congestive heart failure, Diabetes Melitus Type 2, Dengue Haemorrhagic fever (DBD), Hyperplasia of prostate (BPH), Fetus and newborn affected by caesarean delivery, Fever, uspecified/Hyperpyrexia NOS, Dlivery by amergency caesarean section. Kata Kunci : Data Warehouse, Rumah Sakit, Penyakit Pasien, Morbiditas ABSTRACT Hospital morbidity data. Regions are derived from medical record documents of inpatients. Reports of inpatient morbidity are used as an evaluation of drug supply planning, disease data and can be used as decision-making material for making health development planning programs. The inpatient data used is patient data from 2018 - 2019, with a total of 350 patients. The disease data of inpatients is processed using the data warehouse. From data processing the 10 disease data are Typoid Fever, Diarrhoea and gastroenteritis of presumed infectious orgin (Diarrhea), Chronic renal failure, unspecified (CKD), Congestive heart failure, Diabetes Mellitus Type 2, Dengue Haemorrhagic fever (DBD), Hyperplasia of prostate (BPH), Fetus and newborn affected by caesarean delivery, Fever, specified/Hyperpyrexia NOS, Livery by amergency caesarean section. Keywords: Data Warehouse, Hospital, Patient Disease, Morbidity